2014
DOI: 10.1002/2013jc009395
|View full text |Cite
|
Sign up to set email alerts
|

Interferometry of infragravity waves off New Zealand

Abstract: Wave interferometry is a remote sensing technique, which is increasingly employed in helioseismology, seismology, and acoustics to retrieve parameters of the propagation medium from twopoint cross-correlation functions of random wavefields. Here we apply interferometry to yearlong records of seafloor pressure at 28 locations off New Zealand's South Island to investigate propagation and directivity properties of infragravity waves away from shore. A compressed cross-correlation function technique is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 90 publications
(170 reference statements)
0
25
0
Order By: Relevance
“…Background IGWs, which are believed to be generated by the nonlinear interaction of sea swell with bathymetry close to shore, have much smaller amplitude than destructive tsunamis but are continuously present throughout the ocean (Webb et al 1991;Herbers et al 1995;Aucan and Ardhuin 2013;Godin et al 2014). Over extended time periods, the contribution of the background IGWs into the flux of mechanical energy from the ocean into the upper atmosphere is expected to dominate over the contributions of tsunamis.…”
Section: Radiation Of Atmospheric Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Background IGWs, which are believed to be generated by the nonlinear interaction of sea swell with bathymetry close to shore, have much smaller amplitude than destructive tsunamis but are continuously present throughout the ocean (Webb et al 1991;Herbers et al 1995;Aucan and Ardhuin 2013;Godin et al 2014). Over extended time periods, the contribution of the background IGWs into the flux of mechanical energy from the ocean into the upper atmosphere is expected to dominate over the contributions of tsunamis.…”
Section: Radiation Of Atmospheric Wavesmentioning
confidence: 99%
“…But tsunamis are only a transient feature of a more general phenomenon: infragravity waves (IGWs) (Webb et al 1991;Herbers et al 1995;Aucan and Ardhuin 2013;Godin et al 2014). IGWs are permanently present surface gravity waves in the ocean with periods longer than the longest periods (approximately 30 s) of wind-generated waves.…”
Section: Introductionmentioning
confidence: 99%
“…Using an array of pressure gauges in the southwestern Pacific off the South Island of New Zealand, Godin et al [2014] observed strong directionality of the infragravity wavefield with the northwest coast of the South Island acting as a net source of infragravity wave energy. Webb et al [1991] studied deep water infragravity waves in the Pacific during November 1988 and identified infragravity waves originating from the Gulf of Alaska, the northwest Pacific and the southern tip of South America, but little from the southern ocean or tropical western Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…Power spectra of the recorded noise have multiple sharp peaks, which is typical of shipping noise. To suppress the effects of a rapid variation of the noise power spectrum with frequency, we followed Godin et al [21] and evaluated the noise cross-correlation as a Fourier transform of the coherence function, rather than the cross-spectrum. This is equivalent to pre-whitening and normalization of the noise spectrum in each data segment and can be viewed as a frequency-domain counterpart of "one-bit correlation" in the time domain [12], which has been extensively utilized in noise interferometry.…”
Section: Methodsmentioning
confidence: 99%